Effectiveness Of Tax Collection With Warning Letters and Forced Letters On East Medan Pratama KPP Tax Revenue - Latersia Br Gurusinga; Hermawan Sutanto; Feebee Salim (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
This research aims to determine the level of effectiveness of tax collection with warning letters and forced letters on East Medan KPP Pratama tax revenues during the period January - October 2023. The population in this study are individual taxpayers and the research data was obtained from the Medan Pratama Tax Service Office. east. The research method used is the documentation data collection method obtained from KPP Pratama Medan Timur. The results of this research show that tax collection using warning letters and forced letters is less effective, with the calculation results of the average issuance of warning letters being 68.26% and forcing letters being 67.87%. It is said to be less effective because the percentage is in the range of 60% - 80%.